Sales Growth as a Value Catalyst: Financial Performance in Indonesian Manufacturing - Rizky Helmiza; Perdana Wahyu Santosa; Any Setianingrum (SAN Scientific, 2026)
Indonesia's economic growth between 2017-2023 experienced increasing instability, influenced by various factors, including the pandemic. This condition adversely affected the financial performance of most industries, with many reporting significant losses. However, the consumer goods manufacturing sector demonstrated greater resilience compared to other sectors. This study posits that changes in financial performance influence firm value, which in turn affects stock price movements. As such, firm value is considered a critical indicator for investors in making investment decisions, as it reflects a firm's prospects and sustainability. This study aims to examine the effects of profitability, leverage, and firm size on firm value, with sales growth as a moderating variable, among manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (BEI) during the 2017–2023 period. A quantitative research approach was employed, using panel data regression analysis in e-Views 12. The study population comprised 52 companies, of which 28 were purposively selected, yielding 168 observations. The findings reveal that profitability, leverage, and firm size simultaneously affect firm value. Partially, profitability and sales growth do not have a significant effect on firm value, whereas leverage and firm size do.